Towards sustainable resource management in the European Union - Stefan Bringezu (Wuppertal Institut für Klima, Umwelt, Energie, 2002)
A policy framework for sustainable resource management (SRM) is required bothto guarantee the materials and energy supply of the EU economy and safeguardthe natural resource basis in the future. Goals and strategies for sustaining themetabolism of the economy are described. Data are presented on the materialthroughput and physical growth of the EU's economy, on total materialrequirements (TMR), its composition, the decoupling from economic growth, andthe increased shift to other regions. A first future target Material Flow Balance (t-MFB) of the EU is outlined. Detailed data reveal the top ten resource flows.Policy design for SRM should aim at an integrated and balanced approach alongthe material flow, comprising resource extraction, the product cycle and finalwaste disposal. Strategies and potential instruments to manage fossil fuels, metalsand industrial minerals, construction minerals and excavation are discussed.Possible priorities and examples are given for target setting, focusing on limitedexpansion of built-up area, reduced use of non-renewables, increased resourceproductivity, and shift to sustainable cultivation of biomass. – – Eine politische Rahmensetzung für ein Nachhaltiges Ressourcenmanagement (NRM) wird benötigt, um langfristig die Versorgung der EU-Wirtschaft mitMaterialien und Energie ebenso zu sichern wie die natürliche Ressourcenbasis. Ziele und Strategien für einen nachhaltigen gesellschaftlichen Stoffwechsel werden beschrieben. Daten werden vorgestellt zu Stoffdurchsatz und physischem Wachstum der EU-Wirtschaft, ihrem Globalen Materialaufwand (GMA), seiner Zusammensetzung, Abkopplung vom Wirtschaftswachstum und seiner zunehmenden Verlagerung in andere Regionen. Eine erste Zielstoffstrombilanz der EU wird skizziert. Detaillierte Zahlen belegen die Top Ten der Ressourcenflüsse. Die Politik eines NRM sollte auf einen integrierten und balancierten Ansatz entlang des gesamten Stoffstromes von der Ressourcenextraktion, über den Produktzyklusbis zur Entsorgung abzielen. Strategien und potentielle Instrumente für das Management von fossilen Energieträgern, metallischen Rohstoffen, Industrie-mineralien, Baumineralien und Aushub werden diskutiert. Mögliche Prioritätenund Beispiele für Zielsetzungen werden vorgestellt. Der Fokus liegt auf derBegrenzung des Wachstums von Siedlungs- und Verkehrsfläche, der Reduktion des Einsatzes nicht-erneuerbarer Ressourcen, der Erhöhung der Ressourcenproduktivität und dem Umstieg auf nachhaltige Produktionsweisen für Biomasse.
urn:nbn:de:bsz:wup4-opus-13961
Keywords: 330; metabolism of the economy; resource management; material flows; physical growth; strategies for sustainability; total resource requirements; policydesign; target setting; Gesellschaftlicher Stoffwechsel; Ressourcenmanagement; Stoff-ströme; physisches Wachstum; Nachhaltigkeitsstrategien; Globaler Materialaufwand; Politikgestaltung; Zielsetzung; Stoffstrom-Management; Rohstoffpolitik; Umweltpolitik; Nachhaltige Entwicklung; EU-Staaten